2020
DOI: 10.3390/nu13010108
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet Benefit on Cardiovascular Hemodynamics and Erectile Function in Chronic Heart Failure Male Patients by Decoding Central and Peripheral Vessel Rheology

Abstract: Background: Mediterranean diet was evaluated on erectile performance and cardiovascular hemodynamics, in chronic heart failure patients. Methods: 150 male stable heart failure patients were enrolled in the study (62 ± 10 years, New York Heart Association (NYHA) classes I–II, ejection fraction ≤40%). A detailed echocardiographic evaluation including estimation of the global longitudinal strain of the left ventricle and the systolic tissue doppler velocity of the tricuspid annulus was performed. Erectile dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…These findings could be explained by the high use of pesticides in China and Hong Kong, where all three studies reporting neutral or negative results were conducted, although this hypothesis cannot be confirmed. More general concepts of healthy dietary habits 42 or organic food consumption 43 were also reported to be associated with a lower prevalence or development of ED, as was adherence to the Mediterranean diet, most commonly assessed through food‐frequency questionnaires 44–47 . Flavonoid‐rich foods 35,48 and nuts 38,47 were also consumed more frequently by those who did not have ED, likely reflecting a Mediterranean dietary pattern.…”
Section: Resultsmentioning
confidence: 99%
“…These findings could be explained by the high use of pesticides in China and Hong Kong, where all three studies reporting neutral or negative results were conducted, although this hypothesis cannot be confirmed. More general concepts of healthy dietary habits 42 or organic food consumption 43 were also reported to be associated with a lower prevalence or development of ED, as was adherence to the Mediterranean diet, most commonly assessed through food‐frequency questionnaires 44–47 . Flavonoid‐rich foods 35,48 and nuts 38,47 were also consumed more frequently by those who did not have ED, likely reflecting a Mediterranean dietary pattern.…”
Section: Resultsmentioning
confidence: 99%
“…This study results indicated that participants with intermediate adherence to the Mediterranean diet (3 < MDS ≤ 6) had significantly lower odds of COVID-19 incidence (multivariable-adjusted OR = 0.50, 95% CI: 0.34–0.73), and those with the highest adherence (MDS > 6) had the lowest risk (multivariable-adjusted OR = 0.36, 95% CI: 0.16–0.84, p for trend < 0.001) as compared with subjects with MDS ≤ 3. Angelis et al [ 46 ]. mentioned that adherence to the Mediterranean diet has a main impact on cardiovascular diseases and other cardio - metabolic disorders, like diabetes that predisposes to COVID-19 infection and related outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental models, olive oil, a primary substance in the Mediterranean diet, reduced infarct size and protected reperfused myocardium from oxidative damage in vivo. Hyperproteinic, low-carbohydrate, and low-fat diets also demonstrate positive effects on functional capacity; however, RCTs in secondary prevention are scarce [ 45 , 46 , 47 ]. Nutritional education seems to be important for HF patients in order to sustain fluid and salt balance and prevent cachexia through a balanced diet.…”
Section: Nutritional Issues In Chronic Hfmentioning
confidence: 99%